Karakteristik Penderita Gizi Buruk Pada Anak Usia 2-5 Tahun di Rumah Sakit Ibnu Sina Makassar - Fariani Mitha; Sidrah Darma; Aryanti R Bamachry (Pusat riset dan Inovasi Nasional, 2025)
Nutritional problems can jeopardize the survival of a country. The nutritional condition of each individual reflects the physiological demands of that individual, because if these needs are not met, nutrition-related health problems will arise. Children's health and nutritional status are interrelated. When a child's health deteriorates due to an infectious disease, their appetite is affected and they consume less food, resulting in less nutrients entering the body. Journals in this literature review used 3 databases including Google Scholar, PubMed, and Science Direct using the words malnutrition, child, 2-5 years. The literature search was adjusted based on inclusion and exclusion criteria. The search results obtained 10 journals consisting of 4 national journals and 6 international journals. The results showed that the risk factors for malnutrition in children aged 2-5 years were inadequate nutritional intake, parental education and knowledge, infectious diseases, parenting, environmental sanitation and socioeconomic factors.